An evaluation of the relationship between water infrastructure financing and water provision in South Africa - Bapela, Lerato Caroline (My University, 2017)
Whilst previous research has largely blamed inadequate finance as the cause of insufficient water provision and concomitant development implications such as poverty and food production; this thesis, took a slightly different turn and engaged on a critical deconstruction of the relationship between water infrastructure financing and water provision in South Africa. Archival data on South Africa between 1994 and 2014 were collected on water provision, water-asset finance, governance effectiveness, corruption, violence, accountancy and voice. Data were analysed using the OLS regression fixed effect. Findings from the analysis showed that against popular belief, there was lack of significant relationship between water asset finance and water provision. However, nonfinancial variables namely corruption, social violence, accountability and voice of citizens in development decisions showed a significant relationship with water provision. In addition, the analysis showed that water provision is significantly related to cereal production and incidence of poverty. Therefore, the thesis emphasized that rural development could be enhanced through an improved effort on water provision, which would increase cereal production and reduce the incidence of poverty. It stressed however, that provision of water asset finance without attention and control of nonfinancial variables might have the tendency to derail water provision initiatives in South Africa. The thesis made an original contribution by proposing a conceptual framework for employing and researching the catalyst for water provision in South Africa. It also developed three novel research models for future research. Key words: Infrastructure financing, water infrastructure, water provision, water and development, governance, accountability, poverty reduction
Thesis (Ph. D. (Administration Development Planning and Management)) -- University of LImpopo, 2017
Keywords: Infrastructure financing; Water infrastructure; Water provision; Water and development; Governance; Poverty reduction; Municipal water supply - Law and legislation